2016
DOI: 10.1007/s00436-016-4962-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the ectoparasite fauna between micromammals captured in natural and adjacent residential areas are better explained by sex and season than by type of habitat

Abstract: We compared the ectoparasite fauna in 608 micromammals (chiefly 472 wood mice Apodemus sylvaticus, 63 Algerian mice Mus spretus, and 51 greater white-toothed shrews Crocidura russula) captured in natural and adjacent residential areas in spring and autumn during three consecutive years in four areas in periurban Barcelona (NE Spain). We found little support for an association of urbanization with differences in infestation by ectoparasites. Prevalence of Rhipicephalus sp. tick in wood mice and shrews was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
4
9
1
Order By: Relevance
“…Infestation by fleas, the most important vectors for Bartonella (Gutiérrez et al, 2015), was prevalent among the analyzed individuals, but we found little support for an effect of urbanization on prevalence of infestation by arthropods (Cevidanes et al, 2016). However, we found that one flea (Leptopsylla taschenbergi) showed marked differences in prevalence between seasons in natural areas, but prevalence was constant in residential areas, suggesting that narrower variations in environmental factors may had enhanced the survival probabilities in these habitats (Cevidanes et al, 2016). However, no such differences were found for other species of flea, which were more influenced of other factors such as season and host sex (Cevidanes et al, 2016).…”
Section: Introductioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Infestation by fleas, the most important vectors for Bartonella (Gutiérrez et al, 2015), was prevalent among the analyzed individuals, but we found little support for an effect of urbanization on prevalence of infestation by arthropods (Cevidanes et al, 2016). However, we found that one flea (Leptopsylla taschenbergi) showed marked differences in prevalence between seasons in natural areas, but prevalence was constant in residential areas, suggesting that narrower variations in environmental factors may had enhanced the survival probabilities in these habitats (Cevidanes et al, 2016). However, no such differences were found for other species of flea, which were more influenced of other factors such as season and host sex (Cevidanes et al, 2016).…”
Section: Introductioncontrasting
confidence: 81%
“…However, we found that one flea (Leptopsylla taschenbergi) showed marked differences in prevalence between seasons in natural areas, but prevalence was constant in residential areas, suggesting that narrower variations in environmental factors may had enhanced the survival probabilities in these habitats (Cevidanes et al, 2016). However, no such differences were found for other species of flea, which were more influenced of other factors such as season and host sex (Cevidanes et al, 2016). In consequence, in the present study we aimed to get insight on the factors related to the prevalence of Bartonella in micromammals and their fleas in a Mediterranean peri-urban environment.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Higher Leptospira prevalence has been frequently associated with species occupying urban habitats (Andersen‐Ranberg et al., ), but this refers mostly to species such as Rattus spp., which are underrepresented in our wood mouse‐dominated sample (both in natural and residential areas). We also failed to detect differences between habitats in the ectoparasites infesting and Bartonella infecting these same micromammals (Cevidanes, Proboste, Chirife, & Millán, ; Cevidanes et al., ), suggesting that climatic conditions are relatively similar between residential and natural habitats. Mammal dispersal between natural and residential areas could also explain the lack of differences in Leptospira prevalence.…”
Section: Discussionmentioning
confidence: 73%